Understanding the distribution of cattle production systems in the South American Chaco - Fernandez, Pedro David; Kuemmerle, Tobias; Baumann, Matthias; Grau, Héctor Ricardo; Nasca, Jose Andres; Radrizzani Bonadeo, Alejandro; Gasparri, Néstor Ignacio (Taylor and Francis, 2021)
Impacts of cattle production vary among different production systems, but data on their distribution is scarce for most world regions. In this work, we combine datasets on cattle vaccination locations and land cover in a regression framework to define and map major cattle production systems in the Argentinean Dry Chaco. We also explore how cattle occurrence relates to spatial determinants. Results indicate that the region harbors about 5.5 million heads. Cattle density was mainly described by the share of pasture (69.9%), cropland (28.1%) and aridity (23.8%). We identified 12-major cattle production systems: six cow-calf, three whole-cycle, and three fattening systems. Of these, four systems had high woodland cover (>85%). Data generated is available in a website. Understanding the distribution of cattle production systems is important to assess the environmental impacts of beef production at broad scales. Integrating vaccination data with land-cover information provides a promising avenue to identify livestock systems.